From Amazon To Bali: A Journey Through Myths - Igor Igor Amanajás (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
This article aims to report practical intercultural experiences in the experimental choreographies’ creation relating characters from the Brazilian Amazonian culture under the structure and movement bases belonging to traditional Balinese mask dance-dramas. From aesthetic rules pertaining to classical dance, after ten years of training with the master I Made Djimat and his family, in Batuan village, there is a need to elaborate choreographic compositions based on characters from the artist’s Amazon mythology who seeks to narrate the roots of its people and culture through Balinese dances learned over a decade of dedication and refinement of its techniques. More than an artistic experience, it is a rediscovery of origins that presupposes the intersection of myths that are similar despite their divergent homelands. The choreographic composition uses Balinese masks, costumes, music and movements that were integrated with native Amazonian cultural elements. The research aims to find out which elements are viable in the crossing of cultures (Bali-Brazil) regarding the development of new creations. Other questions arise from this study, such as: How can one experience interculturality so that none of the cultures lose their roots, thus maintaining their traditional knowledge? The mythical character in development for this study is a bird of prey that, at night, flies over the villagers’ houses announcing ill omen. The next morning, the bird, already transformed into an old witch, goes through the same houses announcing her arrival with a whistle. The residents then, to avoid the old witch’s curses, present her with coffee, tabacco and fish. Such myth is structured basing its composition of movements and choreographies on traditional characters from Balinese culture such as Garuda and Matah Gede, among others.